Stupor et mirabilia. The Ascent of an Early Modern Redeemer - Unn Falkeid (Scienza & Politica, 2022)
Saint Birgitta of Sweden (1303–1373), one of the most powerful visionary women from the late Middle Ages, was celebrated as a prophet and a sibyl long into seventeenth century. A common suggestion has been that Birgitta’s prophetic status was crafted by her supporters after her death. My claim, however, is that the construction of the prophet was the result of a highly conscious strategy which followed Birgitta from the very beginning of her visionary career, and to which both her supporters and she herself carefully contributed. We meet the traces of such a construction in the earliest hagiographers’ accounts, in the confessors’ ardent supports, and in the many witnesses from the canonization process. Yet, the strongest testimonies of the prophet in spe, is to be found in Birgitta’s own revelations, which is the focus of this article.